5(-2x)-3(4+4x)=0

Simple and best practice solution for 5(-2x)-3(4+4x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-2x)-3(4+4x)=0 equation:


Simplifying
5(-2x) + -3(4 + 4x) = 0

Remove parenthesis around (-2x)
5 * -2x + -3(4 + 4x) = 0

Multiply 5 * -2
-10x + -3(4 + 4x) = 0
-10x + (4 * -3 + 4x * -3) = 0
-10x + (-12 + -12x) = 0

Reorder the terms:
-12 + -10x + -12x = 0

Combine like terms: -10x + -12x = -22x
-12 + -22x = 0

Solving
-12 + -22x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -22x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + -22x = 0 + 12
-22x = 0 + 12

Combine like terms: 0 + 12 = 12
-22x = 12

Divide each side by '-22'.
x = -0.5454545455

Simplifying
x = -0.5454545455

See similar equations:

| 16+2p-11=15 | | 3y-15+7=4 | | -25.294-.8a=-3.2+2.7(2.7a+5.6) | | 4x+2-2x=9 | | X+30=52-x | | 17=6x+5-3x | | 15-100=x | | 0.01*0.9= | | x^8+8x^4+15=0 | | (y-2)(x+7)-(-3x-1)(x-7)= | | -6.8(7.9+1.2k)+3.7=4.2k+40.90016 | | 5y+3x+9=0 | | -6.8(1+.395a)=5.114+4.3a | | (-3x+3)(2x+1)= | | 6x+2=10+2 | | x^5+x^4+5x^3+5x^2+4x+4=0 | | 13x-113=4x-5 | | 0.5-0.6x=-1.9 | | 6x^9(7x+8)= | | (8p+5)(7p-1)= | | 18a+18b+2c+6c-6b-6a= | | 33=log | | 16p+14q+p-3q-4p= | | (-2x^7+6y)(-8x^2-7y^6)= | | 6(3s+10)=258 | | (x-13+4i)(x-13-4i)=equation | | 8m+2n-3m+10n= | | 1.4x=3 | | 4(2x-1)-6x(3x+1)=4-6x | | 16+5z=1 | | x=lx-6l | | 2x-3=7x+9 |

Equations solver categories